IRRIGATION SECTOR IN EUROPEAN UNION: EVOLUTION, CURRENT STATE AND CHARACTERISTICS - Marioara RUSU; Violeta Maria SIMIONESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The irrigation sector is a major issue in European agriculture considering the potential impact of climate change and increasing demand for food in areas undergoing economic development. The main objective of this paper has taken into account the analysis and description of trends and current status of irrigation in the European Union (EU) regarding a series of technological, economic and social factors. Achieving this goal involved literature review and analysis of databases dedicated to the subject. The data analysis targeted irrigable and irrigated agricultural areas, types of used irrigation and types of irrigated crops. Results of the analysis show a picture of the wide variety of irrigation sector in the EU. The development of this sector must consider the multifunctional role of agriculture in establishing a balance between economic, social and environmental variables in different European regions and countries.